2022
DOI: 10.2147/jpr.s346809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single-Shot Erector Spinae Plane Block (ESPB) on Opioid Consumption for Various Surgeries: A Meta-Analysis of Randomized Controlled Trials

et al.

Abstract: Study Objective Pain management plays a pivotal role in enhanced recovery after surgery (ERAS). Erector spinae plane block (ESPB) is widely used in many regions to treat perioperative pain, but its benefits are still somewhat controversial. We, therefore, intent to systematically review the available literature on ESPB, to elucidate its effects on opioid-sparing analgesia, and summarize its potential complications. Design Systematic review of randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 78 publications
(226 reference statements)
0
16
0
2
Order By: Relevance
“…Earlier studies showed no connection between local anesthetic dose and duration. [1][2][3][4] Then, in connection with the development of ultrasound-guided techniques, and dose-finding studies focusing on 'how low can you go', evidence started to emerge showing decreased duration with decreased doses. [5][6][7][8][9] Although the evidence between the previous and more recent studies may seem contradictory, the explanation seems to be that the relationship between local anesthetic dose and duration is not linear.…”
Section: Local Anesthetic Volume and Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies showed no connection between local anesthetic dose and duration. [1][2][3][4] Then, in connection with the development of ultrasound-guided techniques, and dose-finding studies focusing on 'how low can you go', evidence started to emerge showing decreased duration with decreased doses. [5][6][7][8][9] Although the evidence between the previous and more recent studies may seem contradictory, the explanation seems to be that the relationship between local anesthetic dose and duration is not linear.…”
Section: Local Anesthetic Volume and Concentrationmentioning
confidence: 99%
“…LAST, however, is not a complication that only occurs in the operating theatre under the care of anaesthesiologists and many non-anaesthesiologists might often not even be aware of LAST, its recognition and treatment. 1 Traditionally, LAST has been expected to occur after unintentional intravascular injection, however toxic plasma concentrations can also occur secondary to systemic absorption after correct local anaesthetic injection in nerve and fascial plane blocks 2 and also intentional intravenous lidocaine infusion. 3 Various preventative measures can potentially reduce the incidence of LAST events.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lately, under ultrasound guidance, regional blocks have been performed more accurately, providing better postoperative analgesia management [7,8]. The erector spinae plane block (ESPB), first described by Forero et al in 2016 for the treatment of thoracic neuropathic pain [9], has proven effective for acute pain control in abdominal, spinal, breast, and other surgeries [10]. As it can block sympathetic nerve fibers and the ventral rami of spinal nerves [11][12][13]and is easier to perform and safer than paravertebral block, it is quickly gaining popularity among anesthesiologists and applied in various surgeries as a part of multimodal analgesic regimens.…”
Section: Introductionmentioning
confidence: 99%